Thermal Aware Process Scheduling for Multicore Processors - Agrawal, Mahima; Mehta, D A (Transactions on Engineering and Computing Sciences, 2024)
Multi-core processors seem to be an alternative way to higher frequencies for increasing microprocessor performance, by handling more work in parallel at lower frequencies. The addition of multiple cores on the same chip results in an increase in power density on the chip which in turn generates large amount of heat. The increased temperature increases leakage current; and negatively aﬀects chip’s performance, reliability and life expectancy. In addition, they release greenhouse gases in the atmosphere and have negative impact on the environment. The study done so far reveals that the issue of high temperature can be solved by assigning and migrating the processes to a cooler core; but this increases migration cost and temporal temperature gradients thereby decreasing the performance. So, in this work the issue of high temperature along with temporal temperature gradients of the cores is addressed at the Operating System level via scheduling of processes. The experiments are performed on an Intel i5-3470 Linux machine. The experimental results reveal reduction in the peak temperature of the processor up to 11.36%, thermal swings in the processor up to 80% and turnaround time of the processes up to 17.24%. The idea of thermal aware scheduler presented in this paper can be applied for scheduling of jobs in data centers and high-performance computers to achieve performance while making computing environmentally friendly.